2021
DOI: 10.1186/s13019-021-01628-2
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative incentive spirometry for preventing postoperative pulmonary complications in patients undergoing coronary artery bypass graft surgery: a prospective, randomized controlled trial

Abstract: Background Postoperative pulmonary complications (PPCs) often occur after cardiac operations and are a leading cause of morbidity, inhibit oxygenation, and increase hospital length of stay and mortality. Although clinical evidence for PPCs prevention is often unclear and crucial, measures occur to reduce PPCs. One device usually used for this reason is incentive spirometry (IS). The aim of the study is to evaluate the effect of preoperative incentive spirometry to prevent postoperative pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
0
17
0
4
Order By: Relevance
“…An earlier RCT conducted by Sweity et al (2021) to assess the effect of preoperative incentive spirometry was compatible with our findings, as the study showed a significant difference between the interventional and control groups in the incidence of postoperative atelectasis, mechanical ventilation duration, and hospital LOS. The median of the amount of arterial blood oxygen and oxygen saturation was significantly improved in the intervention group [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…An earlier RCT conducted by Sweity et al (2021) to assess the effect of preoperative incentive spirometry was compatible with our findings, as the study showed a significant difference between the interventional and control groups in the incidence of postoperative atelectasis, mechanical ventilation duration, and hospital LOS. The median of the amount of arterial blood oxygen and oxygen saturation was significantly improved in the intervention group [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acute or chronic collapse of part or entire lung was defined as atelectasis. [1] 3.2.10. Dyspnea.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…Postoperative pulmonary complications are common after cardiac surgery and the incidences of postoperative pulmonary complications are 30 to 60%. [ 1 ] Postoperative complications increase morbidities, mortality, and the cost of hospitalization. [ 1 , 2 ] Major postoperative complications that affect the quality of life of patients after cardiac surgery are atelectasis, pneumonia, bronchitis, respiratory insufficiency, pulmonary edema, and pleural effusion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations